Cross-sectional study of Trichinella spp in pigs in CDR, Nepal using pepsin digestion and Elisa serology - Santosh Kumar Karn (2018)
This epidemiological cross-sectional study was conducted in five major pig-producing districts of CDR, Nepal from November 2006 to April 2007. A total of 576 slaughtered pigs were randomly selected and diaphragmatic crus muscles (n=551), corresponding sera (n=487) and sera only (n=25) were collected from them. Meat samples were examined by pepsin digestion to evaluate for larvae of Trichinella spp. The sera were investigated using ELISA to evaluate for antibodies against T. spiralis. The doubtful and positive sera from the ELISA test were investigated by end-point ELISA, and the Western blot was used for confirmatory diagnosis. Pepsin digestion did not detect the larvae of Trichinella spp. AB-ELISA showed 2 positive and 14 doubtful results, out of 344 sera analyzed. End-point ELISA and the Western blot had revealed that all 16 samples were truly negative. A questionnaire revealed no rodent control (70%), left over feeding practices (65%), dumping of farm waste (82.5%) and uncooked meat was being used as feed (100%). This study reveals that Trichinella spp has a low prevalence.